El bloque de constitucionalidad - Del rosario Rodríguez, Marcos (Revista de Derecho, 2019)
The constitutionality block from its origins, either from a perspective regulatory orsubstantial perspective, has emerged as a determinant of the task space state supremerecently in favor of human rights, especially the pro persona principle. That is whyfor adequate protection of this principle, as well as the operation of the fuzzy controlof conventionality, requires the existence of the constitutional for a better cause andefficacy to the effectiveness of human rights.
Keywords: Constitutionality block; Constitutional diffuse control; Constitutional supremacy; Human Rights; Pro persona principle